2016
DOI: 10.1002/rcs.1758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of video lag on laparoscopic surgery: correlation between performance and usability at low latencies

Abstract: Objective measures insufficiently describe the impact of latency therefore standard measures of user experience should be incorporated in studies. Even low latencies may be detrimental to laparoscopic surgery. Results from non-experts cannot predict the impact of latency on experienced surgeons. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…The latency threshold for adverse phenomena (stress, shorter working memory, dizziness, nausea), as well as for actual impact on decision‐making, has been established at 300 ms. Although the latencies achieved so far by optic fibre suffice for safe telementoring, the greater quality in data transmission, the possibility of multiconnectivity, and the likely cost reduction (as the system does not rely on a robot) make 5G a more viable option.…”
Section: Discussionmentioning
confidence: 99%
“…The latency threshold for adverse phenomena (stress, shorter working memory, dizziness, nausea), as well as for actual impact on decision‐making, has been established at 300 ms. Although the latencies achieved so far by optic fibre suffice for safe telementoring, the greater quality in data transmission, the possibility of multiconnectivity, and the likely cost reduction (as the system does not rely on a robot) make 5G a more viable option.…”
Section: Discussionmentioning
confidence: 99%
“…The second reason was that the sole purpose of the tests is to measure latency which can be experienced by an operator who is looking at the display and controlling the remote robot mostly based on the video feedback, i.e., user-perceived latency. Previous studies [11] showed that just-noticeable difference (JND, defined as the change in the intensity of a stimulus needed for humans to perceive a difference) for video latency applications was measured to be approximately 15ms.…”
Section: Web Camera Latency Measurements By Using Pps Signalmentioning
confidence: 99%
“…While remote presence systems differ in various purposes and the fields they are deployed in, one common thing they all share is their dependence on the video feedback from the remote plant to the operator. The effect of video latency in remote presence systems has been studied in [11], with telerobotic surgery system as the target application.…”
Section: Introductionmentioning
confidence: 99%
“…One of the drawbacks is the requirement for dedicated communication networks to control the time latency in the loop in which a surgeon performs an action until the result becomes visible. This latency has been the subject of research and should be below 105 msec to avoid deterioration of the performance and user experience [40]. This can presently only be achieved using private networks.…”
Section: Applications Of Vr Ar and Mr In Urologymentioning
confidence: 99%